Anaemia in chronic kidney disease pregnancy. (June 2021) - Morton, Adam; Burke, Michael; Morton, Anthony; Kumar, Sailesh
Aim: To review the incidence and management of anaemia and outcomes in pregnancies in a cohort of Australian women with chronic kidney disease. Methods: A retrospective audit of 63 pregnancies in 52 women with chronic kidney disease. Results: Sixty-eight percent of chronic kidney disease pregnancies were complicated by haemoglobin less than 100 g/L. Iron stores were measured in only 62% of all pregnancies. Serum ferritin was less than 100 ng/ml in 95% of those tested. Erythropoietin-stimulating agents were used in 24 pregnancies (38%). Intravenous iron was used in only nine non-dialysis pregnancies. Conclusion: Greater awareness of the importance of regular measurement of iron stores and appropriate levels for repletion in chronic kidney disease pregnancies amongst health professionals involved in obstetric care may result in earlier detection and treatment of iron deficiency, and potentially improve maternal and fetal outcomes.